HASRAT NANO RIANTIARNO DALAM CERMIN CINTA: KAJIAN PSIKOANALISIS LACANIAN - Ricky Aptifive Manik (POETIKA, 2016)
Literary works known as authors’ desire manifestation.  In its history, a desire comes from the feeling of the lack of subject.  Writing a literary work becomes an effort to hide it.  The effort can be seen through an author’s point of view on ego ideal in his works.  Novel of Cermin Cinta is chosen as a sample in order to search what and how Nano Riantiarno’s desires are.  The aim is to find out the reflecting of Nano’s ego ideal.  This study uses Lacanian Psychoanalysis (PL).  Metaphor and metonymy will be used through PL in looking deeply the signs of Nano’s desire in Cermin Cinta.  This study finds out that a desire of becoming a writer and an artist has guided Nano unconsciously to other symbolic signs, such as being a ‘tough’,  ‘consistent’, ‘determined’, ‘diligent’ writer, etc. His effort in setting up a theatre community where he becomes the characters writer and director which was reached from the images of Rendra, Putu Wijaya, Arifin C. Noor, and Teguh Karya becomes his desire about the ontological intactness for his identity.  Besides, ‘Freedom’ becomes  ‘object a’ of Nano to get jouissance for himself.